Impact assessment of traffic congestion mitigation policies on transportation network in Hanoi city : Luận văn ThS. Kỹ thuật hạ tầng - Ngo, Thi Mai Loan (2019)
Recently, with the rapid growing economics and urbanization in Hanoi city, there is an increasing of auto – mobilization, This has effected on the level of transport demand, transport patterns and led to the overload of the urban transport infrastructure, causing traffic congestion and environment pollution. Therefore, the city government has approved a number of mechanisms, policies and measures to manage and reduce the role of the private automobile to reduce traffic congestion and protect the environment. This thesis study aims to analyze the impact of traffic congestion mitigation policies of Hanoi city on it's transportation network. The policy will ban the activities of motorcycle in the central districts of Hanoi city by 2030. To do so, this study used a dataset from a stated preference Survey that was designed and conducted from a project of World Bank since 2014. This Survey interviewed total 6047 respondents in the whole 30 districts of Hanoi city. Urban transport modeling was estimated using the internationally common 4-step model (Trip generation, trip distribution, mode choice analysis and trip assignment). This 4-step model helps to pridict transport demand in 2030. Then, a traffic demand forecast system was made based on a demand analysis software called “VISUM”. This traffic demand forecast system will helps to evaluate the impact of ban policy by analysing and then comparing on three different scenarios of Motorcycle ban policies. The results of this study reveal that the ban policy contributes toward reducing traffic congestion. These finding of this study would assess the feasibility and efficiency of the policy and provide useful information on recommendations for the motorcycle ban policy in hanoi city. Furthermore, this would contribute to the planner who doing with urban transport planning of Hanoi and the policy making in making public transport development plan.